Analysis of huanglongbing-associated RNA-seq data reveals disturbances in biological processes within Citrus spp. triggered by Candidatus Liberibacter asiaticus infection - Li, Ruimin; Wang, Xinyou; Hu, Yanan; Huang, Guiyan (Frontiers in Plant Science, 2024)
Huanglongbing (HLB), a disease that's ubiquitous worldwide, wreaks havoc on the citrus industry. The primary culprit of HLB is the gram-negative bacterium Candidatus Liberibacter asiaticus (CLas) that infects the phloem, but its damaging mechanism is yet to be fully understood. In this study, a multitude of tools including weighted correlation network analysis (WGCNA), protein-protein interaction (PPI) network analysis and gene expression profiling are employed to unravel the intricacies of its pathogenesis. The investigation pinpoints various central genes, such as the ethylene-responsive transcription factor 9 (ERF9) and thioredoxin reductase 1 (TrxR1), that are associated with CLas invasion and resultant disturbances in numerous biological operations. Additionally, the study uncovers a range of responses through the detection of differential expressed genes (DEGs) across different experiments. The discovery of core DEGs leads to the identification of pivotal genes such as the sieve element occlusion (SEO) and the wall-associated receptor kinase-like 15 (WAKL15). PPI network analysis highlights potential vital proteins, while GO and KEGG pathway enrichment analysis illustrate a significant impact on multiple defensive and metabolic pathways. Gene set enrichment analysis (GSEA) indicates significant alterations in biological processes such as leaf senescence and response to biotic stimuli. This all-encompassing approach extends valuable understanding into the pathogenesis of CLas, potentially aiding future research and therapeutic strategies for HLB.